2017
DOI: 10.1080/01443615.2017.1318267
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic correlation of foetal neck circumference and area with gestational age among pregnant women in Port Harcourt, Nigeria

Abstract: The purpose of this study was to create a reference range nomogram of foetal neck circumference (FNC) and foetal neck area (FNA) in a Nigerian population using polynomial regression models. This cross-sectional study involved 723 pregnant women between 14 and 40 weeks of gestation. Axial measurements of the FNC and FNA were obtained in three measurements and the mean taken as the final value and the 5th, 50th and 95th percentiles for each foetal gestational age (FGA) were calculated. FNC and FNA correlated str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 17 publications
4
7
0
Order By: Relevance
“…[9] When Abonyi et al also noticed the difference in reference ranges after 30-32 weeks of gestation, they argued that it was caused by the different populations rather than technological improvement. [27] In general, the reference ranges in our study show similarity with the values found by Sherer et al during entire pregnancy period.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…[9] When Abonyi et al also noticed the difference in reference ranges after 30-32 weeks of gestation, they argued that it was caused by the different populations rather than technological improvement. [27] In general, the reference ranges in our study show similarity with the values found by Sherer et al during entire pregnancy period.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, evaluating many parameters to calculate gestational age will increase the reliability rather than evaluating a single sonographic parameter. [24,25] The high correlation between the week of gestation and FNC and FNA measurements was shown in the studies of Hata et al in 1988, Sherer et al in 2007 andAbonyi et al in 2017. [9,26,27] In our study, FNC increased from 4.91±0.72 at 14 weeks of gestation to 17.52±2.11 at 40 weeks of gestation.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We compared data from this study to other similar studies [12,21,22] from different races (Caucasian and African), using their respective centiles. A comparative study of the 50th centile was carried out to rule out any significant difference in values.…”
Section: Discussionmentioning
confidence: 99%
“…This variation is likely to be present among ethnic groups in Africa because genetically individuals are unique as a result of inheritance, geographical location and environmental interactions [18,20]. Consequently, there was a need to establish nomograms for this population without prejudice to a published study conducted in a diverse population whose frame and size are disparate to ours [21]. The study aimed to establish fetal NC nomogram as a predictor of GA estimation in this population and also verify the influence of ethnicity on nomograms.…”
Section: Introductionmentioning
confidence: 99%